THE SMALL - MEDIUM INDUSTRY AND SELF-FULFILLMENT GONTOR DARUL MA’RIFAT STUDENTS ISLAMIC BOARDING SCHOOL IN KEDIRI - REZA FAHMI; PRIMA ASWIRNA; ASNAWIR ASNAWIR (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The theme of the article is